Metrics to measure progress towards climate-smart agriculture (CSA) goals - CGIAR Research Program on Climate Change, Agriculture and Food Security (2016)
Climate-smart agriculture (CSA) aims to achieve the goals of increased productivity / food security, adaptation / resilience, and mitigation. The different weights put on each goal depends on the context. CSA investors and implementers are now seeking methods and sets of indicators to monitor progress towards achieving CSA goals and outcomes as a result of interventions.